An mRNA-Based Respiratory Syncytial Virus Vaccine Elicits Strong Neutralizing Antibody Responses and Protects Rodents Without Vaccine-Associated Enhanced Respiratory Disease - Jianglong Li; Haiyan Long; Shaoyi Chen; Zhendong Zhang; Shuang Li; Qi Liu; Jun Liu; Jiaru Cai; Liping Luo; Yucai Peng (Vaccines)
Background: Respiratory syncytial virus (RSV) causes the most common type of severe lower respiratory tract infection worldwide, and the fusion (F) protein is a target for neutralizing antibodies and vaccine development. This study aimed to investigate the immunogenicity and efficacy of an mRNA-based RSV vaccine with an F protein sequence. Methods: We designed an mRNA construct encoding a modified RSV F protein, which was further developed into an LNP-encapsulated mRNA vaccine (LVRNA007). LVRNA007 was administered to mice and cotton rats, followed by immunogenicity analysis and viral challenge studies. Protection of rodents from the viral infection was evaluated based on the presence of the virus in the lung and pathological examination of respiratory tissues. Results: LVRNA007 induced robust humoral and cellular immune responses in both mice and cotton rats, with neutralization antibody levels in the immunized animals maintained at high levels for over one year. Vaccination of LVRNA007 also protected the rodents from RSV challenge, judged by the much decreased virus titer and the pathological score in the lung tissue. In addition, no vaccine-enhanced disease (VED) phenomenon was observed with LVRNA007 vaccination. Conclusions: Based on the preclinical immunogenicity and efficacy data, LVRNA007 could be a potential promising vaccine for prophylaxis of RSV infection.